2018
DOI: 10.1111/jse.12457
|View full text |Cite
|
Sign up to set email alerts
|

Richness, geographic distribution patterns, and areas of endemism of selected angiosperm groups in Mexico

Abstract: Mexico is a megadiverse country. Presently, 22 126 species of angiosperms have been registered within its territory and 11 001 are considered to be endemic. However, their geographical distributions are far from homogeneous. In addition, Mexico is the center of diversification of several groups. Our analysis focused on such groups. The aims were to identify areas of species richness and endemism. A data matrix with 766 species and 25 579 geographical records was analyzed. It included Calochortus (Liliaceae); B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 82 publications
2
16
0
3
Order By: Relevance
“…These authors identified such areas of endemism towards the center of the country, particularly in the BB and TVB provinces, and highlighted the relevance of Asteraceae species in identifying them. Likewise, Rodríguez et al (2018) pointed out the existence of areas of endemism and centers of high species richness for several groups of angiosperms in the western portion of TVB, coinciding several of them with the areas of endemism found in this study. In the same way, the regions of high vascular plant species richness found by Rzedowski (2020) in Jalisco and Michoacán, coincide with the areas of endemism here identified.…”
Section: Areas Of Endemism In the Transmexican Volcanic Belt Provincesupporting
confidence: 78%
“…These authors identified such areas of endemism towards the center of the country, particularly in the BB and TVB provinces, and highlighted the relevance of Asteraceae species in identifying them. Likewise, Rodríguez et al (2018) pointed out the existence of areas of endemism and centers of high species richness for several groups of angiosperms in the western portion of TVB, coinciding several of them with the areas of endemism found in this study. In the same way, the regions of high vascular plant species richness found by Rzedowski (2020) in Jalisco and Michoacán, coincide with the areas of endemism here identified.…”
Section: Areas Of Endemism In the Transmexican Volcanic Belt Provincesupporting
confidence: 78%
“…Algo similar se ha reportado para la FVTM, pues Suárez-Mota et al (2014) señalan que los sitios ambientales más heterogéneos de esta provincia corresponden a los de mayor riqueza florística. Diversos trabajos han reportado altos niveles de endemismo a lo largo de la FVTM (Sosa & Loera 2017, Sosa et al 2018, Rodríguez et al 2018 y ha sido ampliamente documentada la biodiversidad de esta zona de transición (Suárez-Mota et al 2013, Pinilla-Buitrago et al 2018, Zacarías-Correa et al 2019. Según Rzedowski (1993) y recientemente el trabajo de Sosa & De-Nova (2012), las áreas con el mayor número de especies endémicas en México se concentran en áreas de clima seco, en elevaciones bajas a medias y vegetación xérica, destacando entre otras las regiones de Tehuacán-Cuicatlán, el occidente de la cuenca del río Balsas y la Sierra Gorda, abarcando las provincias biogeográficas FVTM, SMO y SMS; lo que coincide con las áreas con mayor índice de endemicidad de Linaceae (Figura 3).…”
Section: Resultsunclassified
“…Rodríguez et al. (2018) and Halffter et al. (2019) identified the MTZ as a zone evidencing biotic interchange between the Nearctic and Neotropical region with a wide range of environments offering variable ecological niches, inherent for conservation in several plants or animal taxa.…”
Section: Discussionmentioning
confidence: 99%